2011
DOI: 10.1111/j.1752-4571.2011.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × genotype interactions between the toxic cyanobacterium Microcystis and its grazer, the waterflea Daphnia

Abstract: Toxic algal blooms are an important problem worldwide. The literature on toxic cyanobacteria blooms in inland waters reports widely divergent results on whether zooplankton can control cyanobacteria blooms or cyanobacteria suppress zooplankton by their toxins. Here we test whether this may be due to genotype × genotype interactions, in which interactions between the large-bodied and efficient grazer Daphnia and the widespread cyanobacterium Microcystis are not only dependent on Microcystis strain or Daphnia ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 105 publications
(248 reference statements)
6
62
1
Order By: Relevance
“…This large variation in resistance to cyanobacteria in bosminids not only confirms previous studies reporting genetic differences in resistance among Daphnia clones from different populations [8,22,34,35], but also demonstrates that substantial clonal variation can occur within a population since our bosminid clones were randomly isolated from one zooplankton sample. Given that M .…”
Section: Discussionsupporting
confidence: 87%
“…This large variation in resistance to cyanobacteria in bosminids not only confirms previous studies reporting genetic differences in resistance among Daphnia clones from different populations [8,22,34,35], but also demonstrates that substantial clonal variation can occur within a population since our bosminid clones were randomly isolated from one zooplankton sample. Given that M .…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps, clonal variation in response to food stress caused by cyanobacterial filaments was due to a different history of examined clones. Many previous studies have shown that Daphnia genotypes experienced with cyanobacteria in the past can have a greater performance at the next encounter with cyanobacteria in comparison with not experienced genotypes (Lemaire et al 2012;Chislock et al 2013). Although we cannot be sure whether our clones had contact with filamentous cyanobacteria before they have been acquired, the ponds where the Wilson and Zoot clones originate from never-experienced cyanobacterial blooms.…”
Section: Morphological Modifications Of Filtering Apparatus Inmentioning
confidence: 98%
“…However, Microcystis forms colonies under natural conditions, which must be disintegrated before enumeration. Typical techniques for disintegrating Microcystis colonies are sonication (Asai et al 2000;Briand et al 2009;Kurmayer et al 2003;Zhou et al 2012), alkaline hydrolysis (Janse et al 2004;Kardinaal et al 2007;Reynolds and Jaworski 1978), and heating/boiling (Chaffin et al 2011;Joung et al 2006;Lemaire et al 2012;Zohary and Madeira 1987).…”
Section: Introductionmentioning
confidence: 99%